Increases in oil price or oil exports: which one is more positive on trade balance for African OPEC member countries? - Bala, Umar; Lee Chin (Wiley-Blackwell, 2022)
This study examines whether an increase in oil prices or oil exports will improve the trade balance in African OPEC Member Countries. The annual panel data of four African OPEC Member Countries, namely Algeria, Angola, Libya and Nigeria were used in the study. The aim of the study is to determine whether African OPEC Member Countries will benefit more from an increase in oil prices or an increase in oil exports coupled with a depreciation in the exchange rate. Two panel estimators were used, namely a fully modified OLS and a dynamic OLS. The results indicate that both an increase in oil prices and in oil exports will improve the trade balance of African OPEC Member Countries; but the greater benefit will be from an increase in crude oil exports. Furthermore, depreciation in the exchange rate will discourage imports, while it will be insignificant in encouraging exports. Policymakers should know that it will be more beneficial to increase oil exports rather than oil prices in order to improve the trade balance of their country. The oil producing countries are supplying the crude oil based on the equilibrium in the world market demand increase in economic activities is favourable to trade balance. In addition, the central bank has to realise that devaluing the exchange rate is not an effective way to improve exports since it will not lower the price of domestic crude oil.